Technological features of reach stacker operation when stacking containers - Hurieiev, Kostiantyn; Kryvchenkov, Pavlo; Nikolaienko, Denys (КНУБА, 2025)
The technological features of the reach stacker operation in container terminal conditions are considered in the paper. The container stacking schemes and the machine movement path are analyzed, which made it possible to determine the patterns of carrying capacity reduction depending on the stack height and spatial limitations of maneuvering. The calculated dependencies of the reach stacker performance and stability, and recommendations for the operation rational organization are presented.
Keywords: reach stacker; container; stacking; carrying capacity; performance; stability; maneuverability